Associations of 18 F‐RO‐948 tau PET with fluid AD biomarkers, Centiloid, and cognition in early AD continuum - Shekari, Mahnaz; González Escalante, Armand; Milà‐Alomà, Marta; Falcon, Carles; López‐Martos, David; Sánchez‐Benavides, Gonzalo; Brugulat‐Serrat, Anna; Niñerola‐Baizán, Aida; Ashton, Nicholas J.; Karikari, Thomas K.; Lantero‐Rodriguez, Juan; Montoliu‐Gaya, Laia; et al. (Wiley, 2026)
INTRODUCTION
We examined neurofibrillary tangle (NFT) pathology using 18F-RO-948 tau positron emission tomography (PET) in cognitively unimpaired individuals and its associations with amyloid plaques, fluid biomarkers, and cognition in early preclinical Alzheimer's disease (AD).
METHODS
We analyzed 97 participants from the ALFA+ cohort with tau and amyloid PET, magnetic resonance imaging, fluid biomarkers (cerebrospinal fluid [CSF]/plasma), and cognitive data. Braak staging was applied, and correlations with biomarkers and cognitive measures were assessed. Receiver operating characteristic analyses evaluated biomarker performance in predicting tau PET positivity
RESULTS
CSF and plasma tau phosphorylated at threonine 217 (p-tau217) showed the strongest correlation with early Braak I/II tau PET signal (r = 0.58, and r = 0.37, respectively), while plasma p-tau181 and p-tau181/Aβ42 showed moderate associations (r ∼ 0.25). However, positive predictive values were low (PPV = 0.09–0.33).
DISCUSSION
18F-RO-948 PET detected early tau pathology in individuals with low to moderate amyloid load. Fluid biomarkers, especially in plasma, had limited predictive power but high negative predictive value, supporting their use in ruling out early tau pathology in preclinical AD.